Naomi Seidman, Sarah Schenirer and the Bais Yaakov Movement: A Revolution in the Name of Tradition (London; Liverpool: The Littman Library of Jewish Civilization in association with Liverpool University Press, 2019), 434 str. (Časopis za suvremenu povijest, 2020)
Prikaz knjige